Construction of strains of Saccharomyces cerevisiae that grow on lactose. - Sreekrishna, K (1985)
We have constructed strains of Saccharomyces cerevisiae that grow on lactose (Lac+). S. cerevisiae strain YNN27, which, like all S. cerevisiae, is unable to grow on lactose, was transformed with pKR1B-LAC4-1. This plasmid has a selectable marker gene conferring resistance to the antibiotic G418 and carries a 13-kilobase region of the Kluyveromyces lactis genome including LAC4, a beta-galactosidase gene. Transformants were selected first for G418 resistance and then for growth on lactose. Southern hybridization experiments showed that Lac+ transformants had integrated 15-25 tandem copies of the vector into a host chromosome. Several lines of evidence indicate that the Lac+ phenotype in pKR1B-LAC4-1-transformed S. cerevisiae is due to expression of a K. lactis lactose permease gene that lies between 2 and 8.6 kilobase upstream of LAC4 and also to expression of LAC4. The permease gene has been designated LAC12.